The revival of sparto : - Στεφανίδου, Λόη-Ίρις (2015)
Spanish broom (Spartium junceum) or Sparto as it is widely known in Greece, is a plant that grows in most of the Mediterranean countries. This forgotten plant nowadays, used to be a valuable source for manufacturing every day objects such as shoes, ropes or baskets or worked as a substitute for common substances like coffee. People exploited almost every part of the plant; the stems, the leaves, the seeds in various ways and under multiple processes in order to take advantage of the broom's properties and ease their every day life. However the low efficiency of the traditional fiber extraction processes from its branches gradually led to the abandonment of the practices and of the broom itself. The aim of this study is to explore the potentials of Spanish broom fibers in the modern world. Is it possible to compare them with today's most famous fibers such as flax or hemp? Do they have what it takes to adequately stand next to the list with the best fibers in matters of strength and quality? Are the extraction processes competently cheap, fast and with no unbeatable obstacles to be taking about a sufficient production? These and more questions are attempted to be answered in depth.